Powers on Community-Level Deliberation: A Power Cube Approach - Muhammad Taufiq; Suhirman Suhirman; Tubagus Furqon Sofhani; Benedictus Kombaitan (Faculty of Geography, Universitas Gadjah Mada, 2022)
This study is generated by the limited understanding of the actor's power on village-level deliberation. In community-level deliberation, especially for villagers, planning struggles with unbalanced power from involved actors to avoid potential failures due to inappropriate implementation and waste of state finances. Problems from policy formulation results have distorted the consensus. Community-based planning faces different power characteristics displayed by involved actors. However, it seems that this matter's understanding is mostly obtained in Western urban areas context and few have studied it in the rural context, even more, sourced from non-Western and global south practices. Questions arise on the power capabilities each actor has and its implications for the planning formulation results. This article aims to provide an understanding of the actor's position and their source of power. It investigates the power identities of involved actors on the community-level deliberation through a power cube approach. Community-level deliberation in Pematang Tengah village, Indonesian, is used as the case study. Primary data were obtained from interviews with twenty-one respondents, observation, and document analysis during 2018-2020. The result shows that each actor displays a specific power characteristic driving their influences on the planning formulation results. This condition has implications for the construction of the power holder's influence in dominating the deliberation process.